Green Alga, Halimeda macroloba Decaisne in Thailand - มะยะกูล, จารุวรรณ (KKU Science Journal, 2014)
Halimeda macroloba Decaisne (Sarai-Bai-Ma-Kud), flat and fan-shaped segments, a calcified green alga, plays a vital role in marine ecosystem as primary producer, provide shelter and food for marine organisms, reef builder, and the production of calcium carbonate sediments. H. macroloba can produce asexual and sexual reproduction. It has a high growth rate and can produce new segments around 1-2 segments.thallus-1.day-1 or 20.1 mg dry weight.thallus-1.day-1. Populations of H. macroloba range 24-200 thalli m-2 and the plant is abundant and widely distributed both in the Gulf of Thailand and Andaman Sea. H. macroloba can help decreasing dissolved CO2 by mean of photosynthesis and calcification. In Thai waters, calcium carbonate accumulation rate of H. macroloba is 16.6 mg CaCO3. thallus-1.day-1 or 82.46% per thallus. Thus, Halimeda has been recognized as a “carbon sink” species that can decrease CO2